Margaret St. Clair, Forgotten Foremother of Pagan Science Fiction - Clifton, Chas S (Pomegranate, 1997)
The importance of science fiction and fantasy writing in the Pagan community is undeniable. Most often told is the story of how Robert Heinlein’s 1961 novel Stranger in a Strange Land helped spawn the Church of All Worlds.